University Hasanuddin (UNHAS) colloborates with UiTM for post graduate clinical pharmacy and pharmacy practice experience / Norkasihan Ibrahim - Ibrahim, Norkasihan (Faculty of Pharmacy, 2024)
From May 8th to 10th, 2024, the Pharmacy Faculty from the University of Hasanuddin (UNHAS) Indonesia and Universiti Teknologi MARA (UiTM) Malaysia continued their collaborative experience with the program hosted at the UiTM Puncak Alam Campus. The purpose of this academic visit was to strengthen the clinical pharmacy experience for UNHAS postgraduate students. During this visit, UNHAS students had the opportunity to immerse themselves in the Advance Clinical Pharmacy course (PHP733) and acquire significant insights into the daily operations of hospital pharmacy services at both locations: the faculty buildings and Hospital Al-Sultan Abdullah (HASA), UiTM Puncak Alam, Selangor. The UNHAS delegation was led by the Vice Dean of Partnership, Research, and Innovation Faculty of Pharmacy, Professor Yulia Yusrini Djabir and joined by five academic staff and nine postgraduate students.